Justice and Vulnerability in Europe: Justice and Vulnerability in Europe - Dorota Lepianka (Edward Elgar Publishing, 2020)
Justice and Vulnerability in Europe contributes to the understanding of justice in Europe from both a theoretical and empirical perspective. It shows that Europe is falling short of its ideals and justice-related ambitions by repeatedly failing its most vulnerable populations.